Reply: An incomplete story - Cleland, JGF; Flather, MD; Altman, DG; Kotecha, D (Elsevier, 2018)
Beta-blockers reduced mortality in landmark, placebo-controlled trials of heart failure with a reduced left ventricular ejection fraction only for those in sinus rhythm rather than atrial fibrillation (AF), despite use of similar beta-blocker formulations and doses (84% of target) and similar heart rate reductions (1). For patients in AF, neither baseline nor follow-up ventricular rate was associated with beta-blocker benefit, nor have trials comparing rate control intensity shown important differences in outcome, although slower rates may be associated with a worse prognosis (2).